2019
DOI: 10.12944/crnfsj.7.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Process Paramaters of Parboiled Black Rice Using Response Surface Methodology

Abstract: Black rice is well known as healthy food. Nowadays, some people try to change their diet with this rice. However, it still has a problem with long preparation time and hard texture. Parboiling is a hydrothermal process that changes rice starch from crystalline to amorphous. The parboiling process of rice consists of soaking in sodium citrate solution, high-pressure cooking, freezing-thawing and drying. The aim of this research was to find the optimum condition from three processing variables: concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…After leached out, the pigment was well dispered into the surface area of black rice. (Widyasaputra et al, 2019); L * = Lightness; a * = red-green chromatic color; b * = blue-yellow chromatic color Table 3 showed the comparation of cooked rice color parameter between normal, parboiled X and Y black rice. The one way Anova test showed that there was significant difference (α=0.05) between lightness value (L*) of normal black rice and parboiled black rice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After leached out, the pigment was well dispered into the surface area of black rice. (Widyasaputra et al, 2019); L * = Lightness; a * = red-green chromatic color; b * = blue-yellow chromatic color Table 3 showed the comparation of cooked rice color parameter between normal, parboiled X and Y black rice. The one way Anova test showed that there was significant difference (α=0.05) between lightness value (L*) of normal black rice and parboiled black rice.…”
Section: Resultsmentioning
confidence: 99%
“…Parboiling process on black rice had purpose to reduce the cooking time and improve the texture quality (Widyasaputra et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[14] milled rice colour is affected most by steaming and drying times due to higher diffusion of colour pigment from the bran and hull into the endosperm. Also, amino acid milliard reaction present in rice grain has been attributed to influence the colour value of rice as reported by Taghinezhadet al [17].…”
Section: Milled Rice Colour (Mrc)mentioning
confidence: 87%
“…A [17], 65.9% to 70.9% [15], 60.8% to 73.88% [14] and 30.11% to 75.76% [13]. The observed deviations could be due to variations in rice varieties, climate or experimental error.…”
Section: Head Rice Yield (Hry)mentioning
confidence: 99%
See 1 more Smart Citation